Effectiveness of Acetobacter xylinum Bacterial Cellulose Produced from Sugarcane Waste in Accelerating Burn Wound Healing in Animal Test Mice (Mus musculus) - Aqilah, Nabila Zaky; Rosyadi, Hasbiyan (Jurnal Biologi Tropis, 2024)
Burns are often treated inappropriately, such as the use of inappropriate materials, such as butter or toothpaste, thus slowing healing. This study aims to determine the effectiveness of cellulose of Acetobacter xylinum bacteria cultured on sugarcane waste as a wound plaster material for burn wound healing.The research was conducted using a literature study method, analyzing literature related to the cellulose properties of Acetobacter xylinum bacteria, the effectiveness of its use in medical applications, and comparing the results of culture on sugarcane waste media with other sources.The results showed that the cellulose-based wound plaster of Acetobacter xylinum bacteria produced from sugarcane waste has biocompatibility, permeability, and resistance to bacteria that are ideal for accelerating burn wound healing. It can be concluded that wound plasters with Acetobacter xylinum bacterial cellulose from sugarcane waste are an effective alternative for medical applications, especially in burn wound treatment.